Design verification on bored pile within Kenny Hill formation via static load test - Mohamed, Zalina (2010)
Due to variation in soil layers, it is not easy for engineer to be assured that theoretical design of piles comply with the actual site condition. Thus, every design of piled foundations carries its own uncertainty and risk. This study evaluates the applicability of six methods to predict the ultimate bearing capacity of bored pile by static load test at site. Analyses and evaluation were conducted on six bored piles of different sizes and length. The methods are Chin-Kondner’s Method, Brinch Hansen’s Method, DeBeer’s Method, Butler & Hoy’s Method, Fuller & Hoy’s and Decourt’s Method. The pile capacities determined using the different methods were compared with the theoretical method such as semi-empirical method and simplified soil mechanic method within Kenny Hill formation. Results of the analyses show that the best performing method is DeBeer’s Method. Fuller & Hoys’s and Butler & Hoy’s methods is the recommended method for bored pile design practice as it is consistent in predicting the bored pile capability. Chin-Kondner’s method is the over predicted most than the others interpretation methods.